Estimation of Effective Dose in Monte Carlo Simulation Method for CT Coronary Angiography Patients: Life Sciences-Radiology - Deva Sarma, Arnabjyoti; Kanti Singha, Dr.Mrinal; Sharma, Jibon; Pratim Kashyap, Dr. Manash (International Journal of Life Science and Pharma Research, 2023)
Computed tomography (CT) scans of Coronary Angiography have significantly aided in the diagnosis of disorders of the coronary artery. In contrast to other radiological examinations, the patient’s radiation exposure is notably higher. This study aimed to optimize the radiation dose and estimate the adequate amount in computed tomography (CT) for coronary angiography. A total of 380 patients were referred to the Primus Diagnostic Centre and Heath City Hospital, Guwahati Assam, during the study with coronary artery disturbances. Data on the technical parameters used in CT procedures were taken in 2022. The aim and study’s objective was Organ and surface dose to specific radiosensitive organs (Chest) estimation using software imPACT 1.0.4 from National Radiological Protection Board (NRPB) SR250 Monte Carlo dataset. The study population (n = 380) comprised 190 men and 190 women with an average age of 29 to 75 years. The Mean ± SD of BMI and ED are 22.42±1.06 and 21.57±4.27 respectively. The mean DLP is 854.67, and the mean ED is 21.57. The effective doses for males (13- 27) mSv were in females (13-29) mSv. This study was a pioneer in presenting actual amounts of CT examinations in Assam because other countries have already started with more advanced CT procedures, such as dosages for paediatrics, coronary angiography and CT fluoroscopy. With this study, there may be more opportunities to create complex new studies or enhance the data from related studies that may be done in future work. The high precision with minimum risk, the current study can be considered as the need of the hour.